2010
DOI: 10.1097/won.0b013e3181cf7b76
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Ostomy-Related Complications in Korea

Abstract: Education for preventing irritant contact dermatitis, such as proper pouching and peristomal skin protection, and for weight control, should be emphasized in a self-care program for persons living with an ostomy. Preoperative marking by a WOC nurse is needed to reduce the prevalence of flat (flush) stomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 11 publications
3
41
0
11
Order By: Relevance
“…During the follow-up period, DET score increased as time went on in both the SPSC and the CT groups. These results in this study were similar to those reported on skin complications in the peristomal area (Kim et al, 1999;Nybaek & Jemec, 2010;Sung et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During the follow-up period, DET score increased as time went on in both the SPSC and the CT groups. These results in this study were similar to those reported on skin complications in the peristomal area (Kim et al, 1999;Nybaek & Jemec, 2010;Sung et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…However, there was no study performed to measure skin problem after delivering SPSC. Therefore, we determined expected probability of skin problem with reference to the previous studies about ostomy complication in Korea (Park & Kim, 2007;Sung et al, 2010). A sample size of 36 per group was calculated based on an event probability of a 0.4 reduction in the incidence of abnormal peristomal skin status with a type I error of 0.05, 80% power, and 3 time repeated measures.…”
Section: Setting and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…O preparo físico inclui além dos cuidados com a dieta, da administração medicamentosa e do preparo colônico, a demarcação de estoma com ensino pré-operatório, realizada pela enfermeira estomaterapeuta, e isto tem sido apontado como um dos fatores que previnem as complicações de estoma e de pele periestoma (O´SHEA, 2001;COLWELL, FICHERA, 2005;BRAND, DUJOVNY 2008;SUNG et al, 2010;MILLAN et al, 2010;PITTMAN, 2011).…”
Section: Introductionunclassified
“…Com a avaliação sistematizada e periódica da estomia intestinal e da pele periestoma é possível prevenir e identificar complicações mais precocemente, o que possibilita intervenção com rápida resolução. O suporte especializado da enfermagem nessa fase é essencial para a adaptação à condição de estomizado intestinal (PAULA, SANTOS, 1999;BRAND, DUJOVNY 2008;SALVADALENA, 2008;NYBAEK et al, 2009;SUNG et al, 2010;PITTMAN, 2011;MILLAN, et al, 2010 Independente da estratégia de ensino desses pacientes é importante apresentar um espaço para esclarecimentos de dúvidas e demonstração prática desses cuidados para assegurar um aprendizado significativo (LO et al, 2010).…”
Section: Introductionunclassified